Multiple sclerosis risk sharing scheme: two year results of clinical cohort study with historical comparator. (2nd December 2009) - Boggild, Mike; Palace, Jackie; Barton, Pelham; Ben-Shlomo, Yoav; Bregenzer, Thomas; Dobson, Charles; Gray, Richard
Abstract : Objective To generate evidence on the longer term cost effectiveness of disease modifying treatments in patients with relapsing-remitting multiple sclerosis. Design Prospective cohort study with historical comparator. Setting Specialist multiple sclerosis clinics in 70 centres in the United Kingdom. Participants Patients with relapsing-remitting multiple sclerosis who started treatment from May 2002 to April 2005 under the UK risk sharing scheme. Interventions Treatment with interferon beta or glatiramer acetate in accordance with guidelines of the UK Association of British Neurologists. Main outcome measures Observed utility weighted progression in disability at two years' follow-up assessed on the expanded disability status scale (EDSS) compared with that expected by applying the progression rates in a comparator dataset, modified for patients receiving treatment by multiplying by the hazard ratio derived separately for each disease modifying treatment from the randomised trials. Results In the primary per protocol analysis, progression in disability was worse than that predicted and worse than that in the untreated comparator dataset ("deviation score" of 113%; excess in mean disability status scale 0.28). In sensitivity analyses, however, the deviation score varied from −72% (using raw baseline disability status scale scores, rather than applying a "no improvement" algorithm) to 156% (imputing missing data for year two from progression rates for year one). Conclusions It is too early to reach any conclusion about the cost effectiveness of disease modifying treatments from this first interim analysis. Important methodological issues, including the need for additional comparator datasets, the potential bias from missing data, and the impact of the "no improvement" rule, will need to be addressed and long term follow-up of all patients is essential to secure meaningful results. Future analyses of the cohort are likely to be more informative, not least because they will be less sensitive to short term fluctuations in disability.